Hippocampal connectivity changes after traumatic memory reactivation with propranolol for posttraumatic stress disorder: a randomized fMRI study - E. Very; A. Leroy; L. Richaud; G. Vaiva; R. Jardri; P. Roullet; S. Taib; A. Bourcier; I. Loubinoux; P. Birmes (European Journal of Psychotraumatology)
Background: Reactivation of traumatic memory under the influence of propranolol has shown encouraging clinical results in the treatment of posttraumatic stress disorder (PTSD), but the neural correlates remain unknown. To identify these correlates, we examined the changes in brain functional connectivity specifically associated with the influence of propranolol and their correlation with improvement in PTSD symptoms.Objectives: To identify resting-state functional connectivity (rs-FC) changes specifically associated with propranolol after a traumatic memory reactivation procedure (TMRP) in PTSD patients.Method: Thirty patients (50% of women) with PTSD were enrolled in a randomized controlled study comprised of six sessions of a traumatic memory reactivation procedure (TMRP) under the influence of propranolol (n = 16), compared to the same reactivation under a placebo (n = 14). Patients were scanned twice by functional magnetic resonance before and after treatment. Resting state functional connectivity (rs-FC) was compared across groups and over time.Results: Post versus pretreatment comparisons found an increase in rs-FC between the right hippocampus and the left parahippocampal gyrus in the propranolol group, but not in the placebo group. Symptom improvement in both groups were associated with an increase in rs-FC between the parahippocampal gyrus and both the supramarginal gyrus and the amygdala.Conclusions: During TMRP treatment, propranolol appears to constrain functional connectivity changes in the explicit memory brain system. These findings require further replication and exploration but could distinguish the effect of TMRP on the brain from other forms of PTSD psychotherapy.